2019
DOI: 10.1021/acs.orglett.9b02572
|View full text |Cite
|
Sign up to set email alerts
|

Reductive C–O, C–N, and C–S Cleavage by a Zirconium Catalyzed Hydrometalation/β-Elimination Approach

Abstract: A zirconium catalyzed reductive cleavage of Csp3 and Csp2 carbon–heteroatom bonds is reported that makes use of a tethered alkene functionality as a traceless directing group. The reaction is successfully demonstrated on C–O, C–N, and C–S bonds and proposed to proceed via a hydrozirconation/β-heteroatom elimination sequence of an in situ formed zirconium hydride catalyst. The positional isomerization of the catalyst further enables the cleavage of homoallylic ethers and the removal of terminal allyl and prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…However, the selective remote 1,1‐diboration of simple and bulk internal alkenes has not yet been reported. It is well‐known that a stoichiometric amount of a zirconium‐reagent can mediate the isomerization of double bonds, and one catalytic system has recently been reported . We thus became interested in exploring whether the isomerization of internal alkenes to terminal alkenes and a subsequent selective 1,1‐diboration could be achieved using our system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the selective remote 1,1‐diboration of simple and bulk internal alkenes has not yet been reported. It is well‐known that a stoichiometric amount of a zirconium‐reagent can mediate the isomerization of double bonds, and one catalytic system has recently been reported . We thus became interested in exploring whether the isomerization of internal alkenes to terminal alkenes and a subsequent selective 1,1‐diboration could be achieved using our system.…”
Section: Methodsmentioning
confidence: 99%
“…It is well-known that a stoichiometric amount of a zirconiumreagent can mediate the isomerization of double bonds, [22] and one catalytic system has recently been reported. [23] We thus became interested in exploring whether the isomerization of internal alkenes to terminal alkenes and a subsequent selective 1,1-diboration could be achieved using our system. To our delight, a variety of internal alkenes with different chain lengths and positions of the double bond worked well in our system (Scheme 4).…”
Section: Zuschriftenmentioning
confidence: 99%
“…Naphthalen-2-ol (2p) 22 The title compound 2p was prepared from 1p (87.7 mg, 0.3 mmol) at 80 °C according to the general procedure II; white solid; yield: 39.3 mg (91%) (eluent: PE/EtOAc 100:1 to 30:1); R f = 0.66 (PE/EtOAc 5:1). 1 H NMR (400 MHz, CDCl 3 ):  = 7.83-7.75 (m, 2 H), 7.69 (d, J = 8.2 Hz, 1 H), 7.46 (t, J = 7.4 Hz, 1 H), 7.37 (t, J = 7.4 Hz, 1 H), 7.19-7.12 (m, 2 H), 5.71 (s, 1 H).…”
Section: 3′-di(thiophen-3-yl)-(11′-biphenyl)-2-ol (2n)mentioning
confidence: 99%
“…Hu [26,27], Martin [28][29][30], Zhu [31][32][33][34][35][36], and Hartwig [37] recently demonstrated that nickel was a prominent catalyst in chain walking chemistry. Streuff reported a zirconium catalyzed deallylation through chain walking mechanism [38]. Inspired by these reports and our interest in group transfer reactions [39] and nickel-catalyzed reactions [40], we envisaged that the nickel-hydride complex I formed through en route nickel-boryl [41][42][43] water or methanol addiction intermediate σ-bond metathesis would trigger the chain walking process (III, Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%